2020
DOI: 10.3791/60583
|View full text |Cite
|
Sign up to set email alerts
|

Proof-of-Concept for Gas-Entrapping Membranes Derived from Water-Loving SiO<sub>2</sub>/Si/SiO<sub>2</sub> Wafers for Green Desalination

Abstract: Desalination through direct contact membrane distillation (DCMD) exploits water-repellent membranes to robustly separate counterflowing streams of hot and salty seawater from cold and pure water, thus allowing only pure water vapor to pass through. To achieve this feat, commercial DCMD membranes are derived from or coated with water-repellent perfluorocarbons such as polytetrafluoroethylene (PTFE) and polyvinylidene difluoride (PVDF). However, the use of perfluorocarbons is limiting due to their high cost, non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…We also hope that our investigation on this widespread and unique insect will inspire rational designs of materials and processes across a wide spectrum of applications. Mushroom-shaped microtrichia of Halobates could inspire coating-free liquid repellence and the prolonged entrapment of air in micro-textures could unleash the potential of common materials in drag reduction [63][64][65][66] , mitigating cavitation 67 , and desalination 68,69 . Grooming strategies of Halobates might inspire new designs for preventing membrane fouling that commonly affect the efficiency of desalination processes 70,71 .…”
Section: Resultsmentioning
confidence: 99%
“…We also hope that our investigation on this widespread and unique insect will inspire rational designs of materials and processes across a wide spectrum of applications. Mushroom-shaped microtrichia of Halobates could inspire coating-free liquid repellence and the prolonged entrapment of air in micro-textures could unleash the potential of common materials in drag reduction [63][64][65][66] , mitigating cavitation 67 , and desalination 68,69 . Grooming strategies of Halobates might inspire new designs for preventing membrane fouling that commonly affect the efficiency of desalination processes 70,71 .…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by these insects, researchers have demonstrated that by carving mushroom-shaped microtexture pillars (21)(22)(23) and microcavities (17,(24)(25)(26)(27)(28) on surfaces, even intrinsically wetting surfaces can trap air when immersed in liquids. While the inherent wettability of materials dictates that the fully filled or the "Wenzel" state (29) should be the thermodynamic minima, air-filled or metastable "Cassie" states (30) can be engineered to persist for longer durations (31).…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that in the near future, the design principles for GEMs might be scaled up using techniques such as 3-D printing . Currently, we are investigating applications of our gas-entrapping surfaces for mitigating cavitation damage 47 , desalination 46,52 , and reducing hydrodynamic drag.…”
Section: Discussionmentioning
confidence: 99%